2006
DOI: 10.1007/s11738-006-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of phenolics in selected crop species and biological activity of these compounds evaluated by sensitivity of Echinochloa crus-galli

Abstract: The Franciszek Górski In sti tute of Plant Phys i ol ogy, Pol ish Acad emy of Sci ences, Niezapominajek 21, 30-239 Kraków, Po land ** De part ment of Soil Man age ment and Plant Cul ti va tion, Ag ri cul tural Uni ver sity of Kraków, Al. Mickiewicza 21, 31-120 Kraków, Po land Cor re spon dence to: hura@ifr-pan.krakow.pl Key words: allelopathy, buck wheat, Echinochloa crus-galli, oat, phe no lic ac ids, rye, spring bar ley, white mus tard Ab stractThe pur pose of this study was to de ter mine the con tent of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
3
9
1
Order By: Relevance
“…In conclusion, our results provide strong evidence of the allelopathic potential of oat biomass due to flavonoid compounds in accord with recent literature data reporting allelopathic activity for phenolic compounds in oats (Baghestani et al 1999;Chon and Kim 2004;Hura et al 2006). …”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, our results provide strong evidence of the allelopathic potential of oat biomass due to flavonoid compounds in accord with recent literature data reporting allelopathic activity for phenolic compounds in oats (Baghestani et al 1999;Chon and Kim 2004;Hura et al 2006). …”
Section: Discussionsupporting
confidence: 92%
“…Hura et al [40] reported that the content of phenolic compounds in buckwheat plants cultivated during two vegetation seasons may differ by a factor of 10. It should be especially stressed that the structures and properties of phenolics vary greatly, affecting extraction conditions and the analytical methods applied which, in turn, considerably affects the determined amounts [5, 6].…”
Section: Resultsmentioning
confidence: 99%
“…[13] Allelopathic properties of barley plants have been connected with the synthesis of phenolic acids such as benzoic, p-hydroxybenzoic, protocatechuic, gentisic, syringic, vanillic, cinnamic, hydroxycinnamic and salicylic acids. [14] The inhibition of weeds growth by barley was also correlated with chlorogenic acids and free hydroxycinnamic acids such as m-, p-, o-coumaric, ferulic, caffeic, 5′-hydroxyferulic and sinapic acids. [15,16] Structural studies on the flavonoids in barley resulted in characteristics of flavanols, flavones and flavonols with diversified substituents.…”
Section: Introductionmentioning
confidence: 99%